A New HPV score System Predicts the Survival of Patients With Cervical Cancers - Hu, Qunchao; Wang, Yani; Zhang, Yuchen; Ge, Yanjun; Yin, Yihua; Zhu, Haiyan (Frontiers in Genetics, 2021)
Persistent high-risk human papillomavirus (hrHPV) infection is confirmed as the major cause of cervical cancer. According to the HPV infection status, cervical cancer could be generalized as following three subgroups: HPV-negative, pure HPV-infection, and HPV-integration. Currently, the impact of HPV status on cervical cancer prognosis remains under dispute. Therefore, we explored the potential correlation between HPV status and clinical outcome of cervical cancer, by establishing a robust prognostic predicting model based on cervical cancer cohort using The Cancer Genome Atlas (TCGA) database. We performed iCluster algorithm incorporating DNA copy number variation, SNP, DNA methylation, mRNA expression, and miRNA expression profile together and classified the cohort into three clusters. According to defined clusters, we established an HPV-score system by weighing resultant gene alterations through random forest and COX model. This prediction tool could help to identify cervical cancer prognosis through evaluating individual HPV infection status and subsequent genetic modification, which might provide insights into HPV-related gene driven cervical cancer treatment strategies, yet its predictive power and robustness need to be further verified with independent cohorts.